Pengaruh Penerapan Pajak Sistem E-Filing, Pemahaman Pajak Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak - Andiani, Lidia -; Mochtar (STIE Malangkucecwara Malang), Reija Hidayat (STKIP PGRI TULUNGAGUNG, 2020)
Tax is an important component of state revenue. The amount of tax contribution can ensure stability for the availability of sources of state revenue. This study aims to determine (1) The effect of the application of e-filing on taxpayer compliance. (2) The effect of understanding tax on taxpayer compliance. (3) The effect of tax sanctions on taxpayer compliance. The population of this research is the taxpayers who use e-Filing at KPP Pratama Batu, Batu City. Sampling used in this study is non-probability sampling with the sampling technique using incidental sampling, the determination of the number of samples calculated using the Slovin formula using 99 samples. The results of this study indicate that the application of the e-Filing system tax, understanding of taxes and tax sanctions has a positive effect on taxpayer compliance.Keywords: e-Filing, Tax Understanding, Tax Sanctions, Taxpayer Compliance